Effects of mobile phone attachment and forced exposure on attitudes towards the ad and the perceived intrusiveness of online advertisements - O'Raghallaigh, Eamonn (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2021)
Numerous studies on advertising intrusiveness can be found in the literature and have demonstrated that there is a link between disruptive and forced exposure advertising and intrusiveness as well as negative emotional and behavioural responses. However, a gap in the literature exists in understanding these relationships in the mobile context and specifically through the lens of mobile attachment. As mobile penetration grows to become the dominant mode of accessing the internet and as we move towards a mobile-first society, understanding the theoretical and managerial implications of these factors impacting mobile advertising is an important and necessary contribution of this research. This study investigated factors affecting participants' perception of intrusiveness and attitudes towards advertisements in different experimental conditions in an online field experiment with a special focus on mobile phone attachment. The factors under study include a forced exposure advertising condition and a cognitive intensity condition. Scale measures of mobile phone attachment (MPA) in three subscales (anxious attachment, addictive attachment and useful attachment) as well as device type data were collected to test for direct and indirect effects on perceived intrusiveness and attitude towards the ad. The field experiment was designed as a website where participants were randomly assigned to the eight different experiment conditions in a 2x2x2 factorial design - (a) high / low cognitive intensity, (b) forced popup / unforced static banner exposure and (c) mobile / desktop device type. At the end of the exposure test, participants completed scales measuring perceived intrusiveness, attitude toward the ad (meaningfulness) and mobile phone attachment. A valid sample of 846 participants was drawn using quota / convenience sampling from a sampling frame provided by a market research company representing the general population of the Republic of Ireland. Data was analysed using covariance-based structural equation modelling techniques and included exploratory factor analysis, construct validity testing, confirmatory factor analysis and structural model testing. Results observed included a direct positive effect of forced exposure on perceived intrusiveness (Beta= 0.458, 95% CI [0.399, 0.513] ***(p<0.001)), a direct negative effect of perceived intrusiveness on attitude towards the ad (Beta= -0.290, 95% CI [-0.383, -0.202] ***(p<0.001)) and a direct negative effect of forced exposure on attitude towards the ad (Beta= -0.087, 95% CI [-0.162. -0.005] *(p<0.05)). For the dimensions of mobile phone attachment, a direct negative effect of useful mobile phone attachment on perceived intrusiveness Beta= -0.193, 95% CI [-0.316, -0.073] **(p<0.01)) and a direct positive effect of addictive mobile phone attachment on perceived intrusiveness (Beta= 0.160, 95% CI [0.027, 0.306] *(p<0.05)) was observed. Furthermore, a direct positive effect of useful mobile phone attachment on attitude towards the ad (Beta= 0.211, 95% CI [0.083, 0.346] ***(p<0.001)) and a direct negative effect of addictive mobile phone attachment on attitude towards the ad (Beta= -0.180, 95% CI [-0.335, -0.035] *(p<0.05)) was observed. Anxious mobile phone attachment did not show any significant effects on perceived intrusiveness or attitude towards the ad. Perceived intrusiveness was also shown to mediate the effect of forced exposure on attitudes towards the ad (Beta = -0.345, 95% CI [-0.474, -0.235], *** (p<0.001)). Device type and task cognitive intensity showed weak or no multigroup or interaction effects in this field experiment. The results demonstrate that mobile phone attachment has an important role to play in understanding how users interact with online advertising. Users exhibiting useful mobile phone attachment tend to perceive ads as less intrusive and have more positive attitudes towards the meaningfulness of ads, whereas, conversely, users exhibiting addictive mobile phone attachment tend to perceive ads as more intrusive and have a more negative attitude towards the ad. It was also observed that anxious attachment did not have significant effects on perceived intrusiveness or attitude towards the ad. Furthermore, perceived intrusiveness has a role to play in mediating the effects of forced exposure on negative attitudes towards advertising. Neither device type or task intensity was shown not to have any moderating effects on perceived intrusiveness or attitude towards the ad. From a theoretical viewpoint, reactance theory in combination with attachment theory is proposed as the mechanism as to why addictively attached users experience high levels of intrusiveness and more negative attitudes towards the ad, while the technology acceptance model is proposed as a mechanism as to why the opposite is observed for users who exhibit useful attachment. As addictive and problematic mobile phone attachment becomes a growing problem in today s ever more connected world, this study reminds advertisers of the negative effects of intrusive advertising and the necessity to juxtapose the fine balance of seeking more advertising impressions and user attention with the negative counterproductive effects forced exposure advertising has in triggering ad avoidance and negative attitudes, ultimately leading to reduced advertising effectiveness. Our study suggests that advertising practitioners should avoid forced exposure advertising in placements where there is a high potential for the user to exhibit addictive attachment, such as gaming and social media, and focus their attention on using forced exposure formats in situations and audience segments where the user is more likely to be accepting of technology and thus accepting of advertising.
APPROVED
Keywords: Mobile Attachment; Online Advertising; Advertising Intrusiveness